Hak Konstitusional Generasi Mendatang atas Lingkungan Hidup Layak : Kajian Hukum Tata Negara terhadap Tanggung Jawab Negara dalam Pembangunan Berkelanjutan - Zilda Khilmatus Shokhikhah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The right to a decent and healthy environment is explicitly guaranteed under Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia. However, in practice, development policies that prioritize economic growth often neglect environmental sustainability and may even compromise the environmental rights of future generations. This article aims to examine the concept of the constitutional rights of future generations to a sustainable environment within the framework of Indonesian constitutional law, and to evaluate the state's responsibilities in achieving sustainable development based on the principle of intergenerational justice. This study employs a normative juridical approach by analyzing constitutional provisions, statutory regulations, legal doctrines, and relevant decisions of the Constitutional Court. In conclusion, the article recommends strengthening the constitutional dimension of environmental protection through environment-based judicial review, reformulating development policies to ensure intergenerational sustainability, and explicitly recognizing the rights of future generations within the Indonesian constitutional legal framework.